2020
DOI: 10.1136/bmjopen-2020-044726
|View full text |Cite
|
Sign up to set email alerts
|

Changes in demand for emergency ambulances during a nationwide lockdown that resulted in elimination of COVID-19: an observational study from New Zealand

Abstract: ObjectiveTo examine the impact of a 5-week national lockdown on ambulance service demand during the COVID-19 pandemic in New Zealand.DesignA descriptive cross-sectional, observational study.SettingHigh-quality data from ambulance electronic clinical records, New Zealand.ParticipantsAmbulance records were obtained from 588 690 attendances during pre-lockdown (prior to 17 February 2020) and from 36 238 records during the lockdown period (23 March to 26 April 2020).Main outcome measuresAmbulance service utilisati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 18 publications
4
20
1
1
Order By: Relevance
“…We utilised novel surveillance data to examine changes in alcohol intoxication-related ambulance attendances during 2020 months associated with significant COVID-19 restrictions in Victoria compared with matched months in 2019. Similar to a New Zealand based study [19] , we found that overall alcoholintoxication related attendances were comparable to, or declined, during early 2020 in response to government announcements. However, alcohol-intoxication attendances did increase as the lockdown progressed, and may represent people using greater amounts of alcohol to cope with extended periods of lockdown.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We utilised novel surveillance data to examine changes in alcohol intoxication-related ambulance attendances during 2020 months associated with significant COVID-19 restrictions in Victoria compared with matched months in 2019. Similar to a New Zealand based study [19] , we found that overall alcoholintoxication related attendances were comparable to, or declined, during early 2020 in response to government announcements. However, alcohol-intoxication attendances did increase as the lockdown progressed, and may represent people using greater amounts of alcohol to cope with extended periods of lockdown.…”
Section: Discussionsupporting
confidence: 84%
“…Ambulance services are part of the frontline health response to acute crises, including alcohol harms, and are frequently the first contact a person has with health services [ 18 , 19 ]. In Victoria (Australia), ambulance services provide universal coverage in both metropolitation and regional areas, and therefore, utilising the surveillance, monitoring, and reporting capacity of ambulance data provides a unique opportunity to examine, and compare alcohol-related harms at the population level [ 18 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…5 The Netherlands experienced a decrease in preventive services in 2020 compared to the same period in 2019. 7 Decreases in other types of resources for emergency care have been documented, such as the reduction in the 20 To our knowledge, our study is the first to document the status of health care utilization in a nationally representative sample of Mexicans within the context of the Covid-19 epidemic. Our results strongly suggest that the pandemic exacerbated problems and limitations of the public health care system in Mexico, which resulted in unequal access.…”
Section: Discussionmentioning
confidence: 80%
“…Most of the previous studies of COVID-19 in the prehospital setting have not focused on patient assessment or diagnostics but rather on demand and performance of the EMS, and occupational safety [1,3,5,[9][10][11]. In a study from Seattle, the EMS had documented the suspicion of COVID-19 in only 50% of cases with an eventual COVID-19 diagnosis [2].…”
Section: Relation Of Results To the Other Studiesmentioning
confidence: 99%